(التعليم والتعلم السياقي في درس مادة ألفية ابن مالك (بالتطبيق على طلبة معهد دار السلام بانيوماس - Enjang Burhanudin Yusuf (Tarling : Journal of Language Education, 2022)
Contextual Teaching and learning is one approach to learning that helps make it easier for students to understand teaching material because this approach has characteristics in the teaching process including Contructivism (contruktivism), Questioning (quistioning), Finding (inquiry), learning community (learning community), Modeling (modeling), reflection (reflection), actual assessment (authentic assessment). Alfiyah book learning is considered as a difficult subject so that many students find many problems in understanding it. Contextual teaching and learning approaches become an alternative that can help students understand alfiyah lessons more easily because they are taught with examples that fit their abilities and with facts that are close to their lives.